MUSEUM SENI RUPA MODERN DI PONTIANAK - Rahma Aulia; Zairin Zain; Valentinus Pebriano (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Museums in general are used to store, maintain, secure and utilize museum collections in the form of cultural heritage objects. Fine arts museums are appreciated through visions with visible media and have a physical form or simply presented as a show. The city of Pontianak does not yet have a place to carry out the function of this fine art museum. The museum collection focuses on modern fine art with long-term loans to the museum. There are some art enthusiasts in Pontianak but there is no place to channel this interest. The design method uses three stages. The first stage, data collection by classifying data as information and facts on a problem. The second stage, the analysis aims to analyze the data that has been obtained. The third stage is systematic and systematic by using images in the form of stages with product results, namely, planning drawings and design reports. The design of the Modern Art Museum in Pontianak uses a green architectural approach, namely building planning that seeks to minimize various harmful influences on human health and the environment. This museum has two floors divided according to functions, namely manager and visitor functions. The facade used is of the 3R type (Reduce, Reuse, Recycle), so the walls use bricks and the windows will use low e-glass material and uPVC frames. The comparison composition of 60:40 for buildings and green land follows the requirements for building a museum.